Strategi AIPAC (America-Israel Public Affairs Committee) dalam Kebijakan AS: Abraham Accords - Wahyudin, Y. A. (Jurnal Hubungan Internasional Indonesia, 2025)
This research aims to explain the strategies employed by the AIPAC interest group in its efforts to influence U.S. foreign policy regarding the ratification of the Abraham Accords. The main issue in this study is how AIPAC has been able to leverage its strategic position to promote the formulation of U.S. foreign policy. This research uses the interest group theory according to Gabriel Almond, to analyze how an interest group functions as part of the political structure to convey the aspirations of society to policymakers. The research method in this writing is a descriptive qualitative method using primary and secondary sources in the form of literature study. The results of this research consist of three main strategies: (1) lobbying policymakers such as Congress and the American executive; (2) shaping public opinion through the media; and (3) collaborating with other interest groups, namely the evangelical Christian group. This research observes that in the ratification of the Abraham Accords, the strategy was successful by relying on the power of lobbying, the influence of public opinion through the media, and the ability to integrate interest groups.